2021
DOI: 10.1371/journal.pone.0252528
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of childfree adults in Michigan (USA)

Abstract: Childfree individuals choose not to have children, which makes them a distinctive group from parents who have had children, not-yet-parents who plan to have children, and childless indivduals who would have liked to have children. Most research on parental status and psychosocial characteristics has not effectively distinguished childfree individuals from other non-parents or has relied on non-representative samples. In this study, we use a representative sample of 981 Michigan adults to estimate the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 72 publications
1
21
0
1
Order By: Relevance
“…In fact, the proportion of people in the Western world who wish to have children is declining (Blackstone & Stewart, 2016; Martinez et al, 2018), while the proportion who do not want children is expanding. For example, Watling Neal and Neal (2021) indicate that in the United States, the estimation of child-free prevalence rates ranged from a low of 2.2% of married women in the 1970s to a high of 9% of married women in 1995 (Abma & Martinez, 2006). Other research estimates placing the prevalence at 6% between 2006 and 2010 (Martinez et al, 2018; Watling Neal & Neal, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the proportion of people in the Western world who wish to have children is declining (Blackstone & Stewart, 2016; Martinez et al, 2018), while the proportion who do not want children is expanding. For example, Watling Neal and Neal (2021) indicate that in the United States, the estimation of child-free prevalence rates ranged from a low of 2.2% of married women in the 1970s to a high of 9% of married women in 1995 (Abma & Martinez, 2006). Other research estimates placing the prevalence at 6% between 2006 and 2010 (Martinez et al, 2018; Watling Neal & Neal, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Watling Neal and Neal (2021) indicate that in the United States, the estimation of child-free prevalence rates ranged from a low of 2.2% of married women in the 1970s to a high of 9% of married women in 1995 (Abma & Martinez, 2006). Other research estimates placing the prevalence at 6% between 2006 and 2010 (Martinez et al, 2018; Watling Neal & Neal, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A respondent who has not had children (i.e., a non-parent) is classified as a not yet parent if they plan to have children in the future, as childless if they want(ed) children but could not have them, or as childfree if they do not want children. This mirrors the approach used by Neal and Neal (2021) to distinguish different types of non-parents, but…”
Section: Reproductive Statusmentioning
confidence: 85%
“…Researchers have indicated differences in life cycle and family experiences among couples who are voluntarily childfree compared to parents, calling for unique approaches or interventions when working with this population (Pelton & Hertlein, 2011). On the other hand, prior research has indicated that there seem to be few differences in personality characteristics or life satisfaction when comparing childfree adults to those with children (Watling Neal & Neal, 2021). A qualitative study of childfree older adult women indicated that nearly all participants reported a strong sense of life satisfaction, but they also indicated the need for and development of resiliency and experiences of feeling stigmatized for their childfree status (*Stahnke et al, 2020).…”
Section: Rationale For Further Examination Of Life Satisfaction In Th...mentioning
confidence: 97%
“…Prior research has indicated that parenthood is frequently perceived as a moral imperative, and childfree adults are perceived as being less psychologically fulfilled (Ashburn-nardo, 2017). Watling Neal and Neal (2021) noted that persons with children or who wanted children held less positive feelings toward childfree individuals. Among a sample of mostly traditional-aged college students, childfree women were perceived as more emotionally troubled and less warm compared to women who were parents, when asked to respond with their perceptions to different scenarios related to childrearing and relationships (Koropeckyj-Cox et al, 2018).…”
Section: Experiences Of Childfree Individualsmentioning
confidence: 99%